Perceived knowledge and practices of nurses regarding immediate post-operative pain management in surgical wards in Rwanda. A descriptive cross-sectional study - Odile Umuhoza; Geldine Chironda; Godfrey Katende; Madeleine Mukeshimana (Elsevier, 2019)
Background: The World Health Organisation (WHO) states that pain is still an issue that needs a multi-disciplinary approach, even though it does not appear on the list of disease burdens. Worldwide, knowledge and practice deficiencies regarding immediate post-operative pain management among nurses remain a pervasive problem. Purpose of the study: The purpose of this study was to assess the perceived knowledge and practice of immediate post-operative pain management among nurses working in surgical wards in Rwanda. Methodology: This study used a descriptive cross-sectional design involving a convenience sample of 131 nurses working in surgical wards. Data was collected using a self-administered questionnaire. Descriptive statistics, Pearson's correlation coefficient and linear regression were used to analyse the data. Results: The majority of the nurses 97 (74%) had high levels of knowledge on immediate post-operative pain management. While 115 (88%) of the nurses had moderate levels of practice with regards to immediate post-operative pain management. Age (21.8 95% CI (21.1-22.5), p = 0.000), gender (20.7 95% CI (20.4-21, p = 0.000), marital status (20.3 95% CI (18.1-22.5), p = 0.000), educational level (22.2 95% CI (21.5-22.5), p = 0.008) and working experience (21 95% CI (20.1-21.9), p = 0.000) were significantly associated with the perceived knowledge of nurses. Yet, only age (33.2 95% CI (32.9-33.6), p = 0.032), educational level (32.2 95% CI (30.8-33.6), p = 0.006) and working experience (32.5 95% CI (32-33), p = 0.031) were significantly associated with the practice of nurses. Simple linear regression analysis showed a weak positive correlation (0.379, p < 0.000) in which the knowledge contributed to the observed practice by 14.4%. Conclusion: Periodic continuance of professional development (CPD) with an emphasis on the skills needs to be conducted, monitored and evaluated by the hospital administration to enhance nurses' skills in pain management for better patient outcomes.